Twisted intramolecular charge transfer and its contribution to the NLO activity of Diglycine Picrate: a vibrational spectroscopic study - Alen, S; Sajan, D; Umadevi, T; Němec, Ivan; Baburaj, M S; Bena Jothy, V; Selin Joy, B H (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2015)
Single crystals of Diglycine Picrate (DGLP) were grown by slow evaporation technique and the vibrational spectral analysis is carried out using FT Raman and FT-IR spectroscopy, supported by Density Functional Theoretical (DFT) computations to derive equilibrium geometry, vibrational wavenumbers and first hyperpolarizability. The vibrational spectra confirm the existence of NH3(+) in DGLP. The influence of Twisted Intramolecular Charge Transfer (TICT) caused by the strong ionic ground state hydrogen bonding between charged species making DGLP crystal to have the non-centrosymmetric structure has been discussed. The Natural Bond Orbital (NBO) analysis confirms the occurrence of strong intermolecular N-H⋯O hydrogen bond. The HOMO-LUMO energy gap and the first order hyperpolarizability were calculated and it supports the nonlinear optical activity of the Diglycine Picrate crystal.
Keywords: molekulární konformace; pikráty; vodíková vazba; Molecular Conformation; krystalizace; nelineární dynamika; Electrons; Optical Phenomena; Ramanova spektroskopie; Crystallization; FT-Raman; DGLP; vibrace; ICT; FT-IR; Picrates; spektroskopie infračervená s Fourierovou transformací; optické jevy; Spectroscopy, Fourier Transform Infrared; Spectrum Analysis, Raman; Vibration; Hydrogen Bonding; Nonlinear Dynamics; elektrony; NBO